2020
DOI: 10.1086/708092
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Option Values and Spillover Damages for Coastal Protection: Evidence from Oregon’s Planning Goal 18

Abstract: Estimating nonmarket benefits for erosion protection can help inform better decision making and policies for communities to adapt to climate change. We estimate private values for a coastal protection option in an empirical setting subject to irreversible loss from coastal erosion and a land-use policy that provides identifying variation in the parcel-level option to invest in protection. Using postmatching regressions and accounting for potential spillovers, we find evidence that the value of the erosion prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Increased erosion creates a fundamental tension between coastal property owners who want to protect their homes and investments, often with hardened shoreline armoring such as sea walls or rip-rap revetments, and the public right to recreate on the coast as codified by the 1967 Beach Bill. Recent research examined the economic value to coastal housing markets generated by state land-use regulations that limit armoring (Dundas and Lewis 2020). Homes in areas with the option of hardening the shoreline for erosion protection sold for 13 to 22 percent more than similar homes without the option of protection.…”
Section: Box 4 Switching From Douglas-fir To Ponderosa Pinementioning
confidence: 99%
“…Increased erosion creates a fundamental tension between coastal property owners who want to protect their homes and investments, often with hardened shoreline armoring such as sea walls or rip-rap revetments, and the public right to recreate on the coast as codified by the 1967 Beach Bill. Recent research examined the economic value to coastal housing markets generated by state land-use regulations that limit armoring (Dundas and Lewis 2020). Homes in areas with the option of hardening the shoreline for erosion protection sold for 13 to 22 percent more than similar homes without the option of protection.…”
Section: Box 4 Switching From Douglas-fir To Ponderosa Pinementioning
confidence: 99%
“…An analysis of climate adaptation behaviors in coastal North Carolina, in the United States, found that shoreline hardening is correlated with high household income, high home value, high population density, and low racial diversity (Siders and Keenan 2020). When shorelines are hardened, the spillover effects harm ecological and structural integrity, development, and property values on adjacent areas (Dundas and Lewis 2020). Equity considerations may include the amount and duration of additional resources allocated to support areas that are adjacent to hardened shorelines.…”
Section: Tier 4: Accommodate Water With Active Risk Reduction Measuresmentioning
confidence: 99%
“…Hence, in examining the determinants of population activity recovery and creating models for predictive recovery monitoring, it is essential to consider more complex spatial processes such as spillover effect. To examine recovery dynamics, spatial econometrics methods have been applied at the CBG level, particularly the spillover; in other words, the effect of independent features at the CBG level upon neighboring CBGs, to explain spatially related phenomena, such as environmental effects (Bai, 2012; Feng et al, 2020; Li et al, 2020), public health impacts (Benjamin-Chung et al, 2017, 2018; Si et al, 2021), and natural hazards (Lima and Barbosa, 2019; Fischer, 2021; Dundas and Lewis, 2020; Lenzen et al, 2019). Such spatial models examine direct and/or indirect effects, in other words, spillover, and total effects of independent variables over dependent variables.…”
Section: Introductionmentioning
confidence: 99%